High-impact ASA rubber powder, composite material and preparation method of high-impact ASA rubber powder

By introducing specific monomers and reactants in the preparation of ASA glue powder, combined with SAN resin and antioxidants, the problem of insufficient impact resistance in composite materials is solved, and the synchronous improvement of impact resistance and tensile performance is achieved. .

CN119264444APending Publication Date: 2025-01-07BINZHOU YONGHONG NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411276424.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing ASA powder has limited toughening effect in composite materials, resulting in insufficient impact resistance and may lead to a decrease in tensile strength. There are few studies on improving impact resistance and tensile performance.

Method used

By introducing monomers such as butyl acrylate and ethyl methacrylate in the preparation process of ASA glue powder, combining emulsifiers, crosslinking agents and initiators, high-impact ASA glue powder is prepared, and SAN resin, Antioxidant and dispersant are combined and extruded using a twin screw extruder to form a high impact composite material.

Benefits of technology

It significantly improves the impact resistance of ASA glue powder and composite materials, while maintaining good tensile resistance and improving the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264444A_ABST
    Figure CN119264444A_ABST
Patent Text Reader

Abstract

The invention discloses high-impact ASA rubber powder, a composite material and a preparation method of the high-impact ASA rubber powder and the composite material, and relates to the technical field of polymer composite materials. Comprising the following steps: mixing butyl acrylate, ethyl methacrylate, an emulsifier, a cross-linking agent, an initiator, a reducing agent and water, and reacting to obtain a seed emulsion; mixing the seed emulsion, butyl acrylate, ethyl methacrylate, an emulsifier, a cross-linking agent, an initiator, a reducing agent and water, and reacting to obtain a core-layer emulsion; adding styrene, acrylonitrile, butadiene, an emulsifier and an initiator into the core-layer emulsion, and reacting to obtain a grafted emulsion 1; adding methylsiloxane, polyethylene glycol terephthalate, an emulsifier and an initiator into the grafted emulsion 1, and reacting to obtain a grafted emulsion 2; and condensing, filtering and drying the grafted emulsion 2 to obtain the high-impact ASA rubber powder, so that the impact resistance of the product can be remarkably improved, and good tensile property can be maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite materials, and in particular to a high-impact ASA rubber powder, a composite material and a preparation method thereof. Background Art

[0002] ASA is a "core-shell" structure grafted polymer obtained by grafting styrene and acrylonitrile monomers onto cross-linked polyacrylate (PBA) rubber particles. The PBA core has a toughening effect, while the SAN (styrene-acrylonitrile copolymer) shell has a volume-increasing effect. Because ASA has this special "core-shell" structure, it can act as an impact modifier. When blended with other polymers, it can improve the toughness of the material, so it is suitable for use as an impact modifier for construction and outdoor materials. ASA resin has excellent weather resistance and will not change color even after long-term exposure to the sun and rain. In addition, ASA material also has excellent chemical resistance and environmental stress cracking resistance, and can withstand hot water treatment and detergent cleaning. The material has been widely used in the exterior products of many automobile OEMs.

[0003] The significant differences between the "core-shell" structured impact modifier and other impact modifiers mainly lie in the molecular structure, degree of cross-linking, grafting range and rubber particle size. Since the above properties are determined during the synthesis process, after being dispersed in the toughened resin matrix, the corresponding size and shape of the particles will remain unchanged and be relatively stable. Therefore, the rubber polymers with "core-shell" structure have excellent comprehensive properties and can be used as impact modifiers to toughen polymers.

[0004] Chinese patent CN117510737A discloses an ASA rubber powder and its preparation method, and a high-gloss ASA resin. The present invention provides an ASA rubber powder, comprising a core and a shell coated on the surface of the core; the core is a butyl acrylate-methacrylic acid copolymer or a butyl acrylate-acrylic acid copolymer; the shell is a styrene-acrylonitrile-methacrylic acid copolymer or a styrene-acrylonitrile-acrylic acid copolymer. The invention uses acrylic acid or methacrylic acid as a copolymer monomer to improve the glossiness of the core and the shell; acrylic acid or methacrylic acid, as a strong polar monomer, enhances the polarity of the ASA rubber powder core, thereby enhancing the compatibility between the core and the shell; in addition, acrylic acid or methacrylic acid, as an acid, is conducive to the agglomeration of the core layer latex particles and improves the impact of the ASA rubber powder.

[0005] Chinese patent CN102161808A discloses an ASA resin with excellent appearance performance and its preparation method, the resin includes the following components and weight proportions: SAN 10-50; acrylonitrile-acrylate-styrene cross-linked modified graft copolymer 50-90; light stabilizer 0.2-0.6; antioxidant 0.2-1; lubricant 0.2-2; the raw materials are sent into a twin-screw extruder after stirring and mixing, and the materials are melted and compounded under the conveying, shearing and mixing of the screw, and then extruded, drawn, cooled and pelletized to obtain acrylonitrile-acrylate-styrene resin with excellent appearance performance. This invention improves the existing injection molding ASA resin, which has uneven gloss, easy to show "iridescent" white spots under strong light, and generally low tinting power, so as to have excellent appearance performance.

[0006] At present, in some application scenarios, due to the limited toughening effect of ASA rubber powder in the composite material system, ASA composite materials still have the problem of insufficient impact resistance. In addition, the addition of ASA rubber powder may also lead to a decrease in tensile strength, and it is necessary to add a modifier to the composite material. At present, there is little research on improving the performance of ASA rubber powder to achieve simultaneous improvement of impact resistance and tensile resistance. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide a high-impact ASA rubber powder, a composite material and a preparation method thereof, which can significantly improve the impact resistance of the ASA rubber powder, further improve the impact resistance of the composite material, and maintain good tensile properties.

[0008] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:

[0009] In one aspect, the present invention provides a method for preparing high-impact ASA rubber powder, comprising the following steps:

[0010] (1) mixing butyl acrylate, ethyl methacrylate, an emulsifier, a cross-linking agent, an initiator, a reducing agent, and water, and reacting them to obtain a seed emulsion;

[0011] (2) mixing the seed emulsion obtained in step (1), butyl acrylate, ethyl methacrylate, an emulsifier, a cross-linking agent, an initiator, a reducing agent, and water, and reacting them to obtain a core layer emulsion;

[0012] (3) adding styrene, acrylonitrile, butadiene, an emulsifier, and an initiator to the core layer emulsion obtained in step (2), reacting to obtain a graft emulsion 1;

[0013] (4) adding methylsiloxane, polyethylene terephthalate, an emulsifier, and an initiator to the grafted emulsion 1 obtained in step (3), and reacting to obtain a grafted emulsion 2;

[0014] (5) The grafted latex 2 obtained in step (4) is coagulated, filtered, and dried to obtain the high-impact ASA rubber powder.

[0015] Preferably, in steps (1) to (4), the emulsifier is selected from at least one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.

[0016] Preferably, in step (1)-step (2), the cross-linking agent is selected from at least one of diisopropylbenzene hydroperoxide and diisopropylbenzene peroxide.

[0017] Preferably, in step (1) to step (4), the initiator is at least one of acyl peroxides (such as benzoyl peroxide, lauroyl peroxide), hydroperoxides (such as cumene hydroperoxide, tert-butyl hydroperoxide), dialkyl peroxides (such as di-tert-butyl peroxide, diisopropyl peroxide), ester peroxides (such as tert-butyl perbenzoate, tert-butyl pervalerate), ketone peroxides (such as methyl ethyl ketone peroxide, cyclohexanone peroxide), and dicarbonate peroxides (such as diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate), and more preferably at least one of benzoyl peroxide, lauroyl peroxide, tert-butyl peroxybenzoate, and dicyclohexyl peroxydicarbonate.

[0018] Preferably, in step (1)-step (2), the reducing agent is selected from at least one of sodium thiosulfate, EDTA (ethylenediaminetetraacetic acid), and ammonium ferrous sulfate, and more preferably EDTA.

[0019] Preferably, in step (1), the mass ratio of butyl acrylate to ethyl methacrylate is 50-500:0.1-5, more preferably 60:1.

[0020] Preferably, in step (1), the mass ratio of butyl acrylate, ethyl methacrylate, emulsifier, cross-linking agent, initiator and reducing agent is 50-500: 0.1-5: 0.1-5: 0.01-1: 0.05-0.5: 1-30, and more preferably 60: 1: 0.8: 0.05: 0.1: 5.

[0021] Preferably, in step (1), the reaction conditions are: temperature 50-60°C, reaction time 4-8h; more preferably: temperature 55°C, reaction time 6h.

[0022] Preferably, in step (2), the added mass of the butyl acrylate, ethyl methacrylate, emulsifier, cross-linking agent, initiator and reducing agent is 1 / 4 to 2 times the added mass of the butyl acrylate, ethyl methacrylate, emulsifier, cross-linking agent, initiator and reducing agent in step (1), respectively, and more preferably 3 / 4.

[0023] Preferably, in step (2), the reaction conditions are: temperature 60-80°C, reaction time 4-8h; more preferably: temperature 75°C, reaction time 4h.

[0024] Preferably, in step (3), the total mass ratio of the styrene, acrylonitrile and butadiene to the total mass ratio of the butyl acrylate and ethyl methacrylate in step (1) is 1:2-15, more preferably 1:4.

[0025] Preferably, in step (3), the mass ratio of styrene, acrylonitrile and butadiene is 3-10:2-8:0.01-0.5, and more preferably 8:7:0.25.

[0026] Preferably, in step (3), the mass ratio of styrene, acrylonitrile, butadiene, emulsifier and initiator is 3-10:2-8:0.01-0.1:0.05-0.5:0.01-0.05, and more preferably 8:7:0.25:0.1:0.01.

[0027] Preferably, in step (3), the reaction conditions are: temperature 70-90°C, reaction time 5-8h; more preferably: temperature 80°C, reaction time 6h.

[0028] Preferably, in step (4), the mass ratio of the total mass of methylsiloxane and polyethylene terephthalate to the mass ratio of butyl acrylate in step (1) is 1:100-1000, more preferably 1:400.

[0029] Preferably, in step (4), the mass ratio of methylsiloxane to polyethylene terephthalate is 1-10:1, more preferably 3:1.

[0030] Preferably, in step (4), the mass ratio of methylsiloxane, polyethylene terephthalate, emulsifier and initiator is 5.25-10:1:0.05-0.5:0.01-0.05, and more preferably 3:1:0.1:0.01.

[0031] Preferably, in step (4), the reaction conditions are: temperature 50-70°C, reaction time 3-6h, heating to 80°C and keeping warm for 2-5 hours; more preferably: temperature 62°C, reaction time 4h, heating to 80°C and keeping warm for 3 hours.

[0032] As a preferred embodiment of the present invention, the method is prepared according to the following steps:

[0033] (1) 120 g of butyl acrylate, 2 g of ethyl methacrylate, 1.6 g of emulsifier, 0.1 g of cross-linking agent, and 10 g of reducing agent were added to 1000 g of deionized water, the temperature was raised to 55° C., 0.2 g of initiator was added, and the mixture was reacted for 6 h under nitrogen protection to obtain a seed emulsion;

[0034] (2) slowly adding a mixture of 90 g butyl acrylate, 1.5 g ethyl methacrylate, 1.2 g emulsifier, 0.075 g cross-linking agent, 7.5 g reducing agent and deionized water to the seed emulsion obtained in step (1), heating to 75° C., adding 0.15 g initiator, and reacting for 4 h under nitrogen protection to obtain a core layer emulsion;

[0035] (3) adding 16 g styrene, 14 g acrylonitrile, 0.5 g butadiene, and 0.2 g emulsifier to the core layer emulsion obtained in step (2), heating to 80° C., adding 0.01 g initiator, and reacting for 6 h to obtain graft emulsion 1;

[0036] (4) adding 0.3 g of methylsiloxane, 0.1 g of polyethylene terephthalate, and 0.01 g of emulsifier to the grafted emulsion 1 obtained in step (3), raising the temperature to 62° C., adding 0.001 g of initiator, reacting for 4 h, raising the temperature to 80° C. and keeping the temperature for 3 hours to obtain a grafted emulsion 2;

[0037] (5) The grafted latex 2 obtained in step (4) is coagulated, filtered, and dried to obtain the high-impact ASA rubber powder.

[0038] In another aspect, the present invention provides high-impact ASA rubber powder prepared according to the above preparation method.

[0039] In another aspect, the present invention provides a composite material, comprising high-impact ASA rubber powder prepared according to the above preparation method, SAN resin, antioxidant and dispersant.

[0040] Preferably, the composite material comprises, in parts by weight, 10-20 parts of high-impact ASA rubber powder prepared according to the above preparation method, 8-15 parts of SAN resin, 0.5-1.5 parts of antioxidant and 0.1-0.5 parts of dispersant.

[0041] Further preferably, the composite material comprises, in parts by weight, 15 parts of high-impact ASA rubber powder prepared according to the above preparation method, 10 parts of SAN resin, 1 part of antioxidant and 0.3 parts of dispersant.

[0042] Finally, the present invention provides a method for preparing the composite material, comprising the following steps:

[0043] The high-impact ASA rubber powder, SAN resin, antioxidant and dispersant in the formula are mixed and granulated by extrusion using a twin-screw extruder.

[0044] The beneficial effects of the present invention are:

[0045] The invention improves the comprehensive performance of ASA by introducing different monomers into the core layer and the shell layer, which can significantly improve the impact resistance of the ASA rubber powder and further improve the impact resistance of the composite material while maintaining good tensile properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is the SEM image of the ASA rubber powder prepared in Example 1;

[0047] Figure 2 TEM image of ASA rubber powder prepared in Example 1;

[0048] Figure 3 This is a SEM image of the fracture surface of the material prepared after granulation of the ASA rubber powder prepared in Example 1. DETAILED DESCRIPTION

[0049] In order to make the technical means, creative features, purpose and efficacy of the present invention easy to understand, the present invention is further explained in conjunction with specific embodiments below, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without creative work all belong to the protection scope of the present invention. In the following embodiments, unless otherwise specified, the operating methods used are conventional operating methods, the equipment used are conventional equipment, and the equipment materials used in each embodiment are the same.

[0050] Example 1

[0051] (1) 120 g of butyl acrylate, 2 g of ethyl methacrylate, 1.6 g of sodium dodecyl sulfate, 0.1 g of diisopropylbenzene hydroperoxide, and 10 g of EDTA were added to 1000 g of deionized water, the temperature was raised to 55° C., 0.2 g of benzoyl peroxide was added, and the mixture was reacted for 6 h under nitrogen protection to obtain a seed emulsion;

[0052] (2) slowly adding a mixture of 90 g butyl acrylate, 1.5 g ethyl methacrylate, 1.2 g sodium dodecyl sulfate, 0.075 g diisopropylbenzene hydroperoxide, 7.5 g EDTA, and 100 g deionized water to the seed emulsion obtained in step (1), heating to 75° C., adding 0.15 g benzoyl peroxide, and reacting under nitrogen protection for 4 h to obtain a core layer emulsion;

[0053] (3) adding 16 g styrene, 14 g acrylonitrile, 0.5 g butadiene, and 0.2 g sodium dodecyl sulfate to the core layer emulsion obtained in step (2), heating to 80° C., adding 0.01 g benzoyl peroxide, and reacting for 6 h to obtain graft emulsion 1;

[0054] (4) 0.3 g of methylsiloxane, 0.1 g of polyethylene terephthalate, and 0.01 g of sodium lauryl sulfate were added to the graft emulsion 1 obtained in step (3) in sequence, the temperature was raised to 62° C., 0.001 g of benzoyl peroxide was added, the reaction was continued for 4 h, the temperature was raised to 80° C., and the mixture was kept warm for 3 hours to obtain a graft emulsion 2;

[0055] (5) The grafted latex 2 obtained in step (4) is coagulated, filtered, and dried to obtain the high-impact ASA rubber powder.

[0056] Example 2

[0057] (1) 100 g of butyl acrylate, 0.2 g of ethyl methacrylate, 0.2 g of sodium dodecyl sulfate, 0.02 g of diisopropylbenzene hydroperoxide, and 2 g of EDTA were added to 1000 g of deionized water, the temperature was raised to 55° C., 0.1 g of benzoyl peroxide was added, and the mixture was reacted for 5 h under nitrogen protection to obtain a seed emulsion;

[0058] (2) slowly adding a mixture of 200 g butyl acrylate, 0.4 g ethyl methacrylate, 0.4 g sodium dodecyl sulfate, 0.04 g diisopropylbenzene hydroperoxide, 4 g EDTA, and 200 g deionized water to the seed emulsion obtained in step (1), heating to 75° C., adding 0.2 g benzoyl peroxide, and reacting for 6 h under nitrogen protection to obtain a core layer emulsion;

[0059] (3) Add 6 g styrene, 4 g acrylonitrile, 0.02 g butadiene, and 0.1 g sodium dodecyl sulfate to the core layer emulsion obtained in step (2), raise the temperature to 80° C., add 0.02 g benzoyl peroxide, and react for 5 h to obtain graft emulsion 1;

[0060] (4) 0.9 g of methylsiloxane, 0.1 g of polyethylene terephthalate, and 0.005 g of sodium lauryl sulfate were added to the graft emulsion 1 obtained in step (3) in sequence, the temperature was raised to 62° C., 0.001 g of benzoyl peroxide was added, the reaction was continued for 4.5 h, the temperature was raised to 80° C., and the mixture was kept warm for 3 hours to obtain a graft emulsion 2;

[0061] (5) The grafted latex 2 obtained in step (4) is coagulated, filtered, and dried to obtain the high-impact ASA rubber powder.

[0062] Example 3

[0063] (1) 100 g of butyl acrylate, 1 g of ethyl methacrylate, 1 g of sodium dodecyl sulfate, 0.1 g of diisopropylbenzene hydroperoxide, and 6 g of EDTA were added to 1000 g of deionized water, the temperature was raised to 55° C., 0.2 g of benzoyl peroxide was added, and the mixture was reacted for 6 h under nitrogen protection to obtain a seed emulsion;

[0064] (2) slowly adding a mixture of 25 g butyl acrylate, 0.25 g ethyl methacrylate, 0.25 g sodium dodecyl sulfate, 0.025 g diisopropylbenzene hydroperoxide, 1.5 g EDTA, and 25 g deionized water to the seed emulsion obtained in step (1), heating to 75° C., adding 0.015 g benzoyl peroxide, and reacting for 4 h under nitrogen protection to obtain a core layer emulsion;

[0065] (3) adding 6 g styrene, 4.8 g acrylonitrile, 0.3 g butadiene, and 0.3 g sodium dodecyl sulfate to the core layer emulsion obtained in step (2), heating to 80° C., adding 0.03 g benzoyl peroxide, and reacting for 5 h to obtain graft emulsion 1;

[0066] (4) 0.21 g of methylsiloxane, 0.04 g of polyethylene terephthalate, and 0.002 g of sodium lauryl sulfate were added to the graft emulsion 1 obtained in step (3) in sequence, the temperature was raised to 62° C., 0.002 g of benzoyl peroxide was added, the reaction was continued for 5 h, the temperature was raised to 80° C., and the mixture was kept warm for 4 h to obtain a graft emulsion 2;

[0067] (5) The grafted latex 2 obtained in step (4) is coagulated, filtered, and dried to obtain the high-impact ASA rubber powder.

[0068] Comparative Example 1

[0069] The difference from Example 1 is that ethyl methacrylate is not added in step (1) and step (2), and the rest is the same.

[0070] Comparative Example 2

[0071] The difference from Example 1 is that butadiene is not added in step (3), and the rest is the same.

[0072] Comparative Example 3

[0073] The difference from Example 1 is that the grafted latex 1 obtained in step (3) is directly condensed, filtered and dried to obtain ASA rubber powder.

[0074] Comparative Example 4

[0075] The difference from Example 1 is that methylsiloxane is not added in step (4), and the rest is the same.

[0076] Comparative Example 5

[0077] The difference from Example 1 is that polyethylene terephthalate is not added in step (4), and the rest is the same.

[0078] Comparative Example 6

[0079] The difference from Example 1 is that in step (4), 0.1 g of methylsiloxane and 0.3 g of polyethylene terephthalate are added, and the rest are the same.

[0080] Preparation Example

[0081] The ASA rubber powder prepared in Examples 1-3 and Comparative Examples 1-5 and the commercially available product (BASF 778T) were respectively prepared into ASA-containing materials according to the following method: 15 parts of ASA rubber powder, 10 parts of SAN resin (LG Chemical, model 82TR), 1 part of antioxidant (BHT264) and 0.3 parts of dispersant (BYK-163) were fully mixed and granulated using a twin-screw extruder, and vacuum dried at 50°C for 16 hours to obtain the ASA-containing material. The conditions of the screw extruder are: 155-165°C in zone 1, 200-210°C in zone 2, 210-220°C in zone 3, 220-230°C in zone 4, 230-240°C in zone 5, 240-250°C in zone 6, 250-260°C in zone 7, 260-270°C in zone 8, 270-280°C in zone 9, rotation speed of 35r / min, and die head pressure of 5MPa.

[0082] Preparation of comparative material: No ASA rubber powder was added to the formula, and the preparation method was the same as above.

[0083] The prepared ASA-containing material was subjected to performance tests: the tensile strength was tested according to GB / T 1040-2006 at a test rate of 50 mm / min; the impact strength was tested according to GB / T 1843-2008; and the bending performance was tested according to GB / T9341-2006 at a test rate of 2 mm / min.

[0084] Test results:

[0085] The test results of ASA-containing materials prepared from different embodiments and comparative examples, commercially available products, and comparative materials are as follows:

[0086] Tensile strength(MPa) <![CDATA[Impact strength (KJ / m 2 )]]> Bending strength(MPa) Example 1 51.4 23.8 2403 Example 2 46.5 25.6 2146 Example 3 47.2 20.7 2317 Comparative Example 1 40.6 21.4 1911 Comparative Example 2 43.1 22.8 2189 Comparative Example 3 39.9 19.3 1925 Comparative Example 4 42.4 22.0 2141 Comparative Example 5 43.6 20.9 1914 Comparative Example 6 44.9 23.4 2002 Commercially available products 41.5 17.6 1883 Comparative Materials 47.7 6.8 2251

[0087] The results show that the high impact resistant rubber powder prepared in Examples 1-3 significantly improves the impact resistance, tensile strength and flexural strength after being prepared into composite materials, while Comparative Examples 1-6 and commercially available products suffer varying degrees of loss in tensile strength and flexural strength.

[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing high impact ASA rubber powder, characterized in that: The following steps are involved: (1) mixing butyl acrylate, ethyl methacrylate, an emulsifier, a cross-linking agent, an initiator, a reducing agent, and water, and reacting them to obtain a seed emulsion; (2) mixing the seed emulsion obtained in step (1), butyl acrylate, ethyl methacrylate, an emulsifier, a cross-linking agent, an initiator, a reducing agent, and water, and reacting them to obtain a core layer emulsion; (3) adding styrene, acrylonitrile, butadiene, an emulsifier, and an initiator to the core layer emulsion obtained in step (2), reacting to obtain a graft emulsion 1; (4) adding methylsiloxane, polyethylene terephthalate, an emulsifier, and an initiator to the grafted emulsion 1 obtained in step (3), and reacting to obtain a grafted emulsion 2; (5) The grafted latex 2 obtained in step (4) is coagulated, filtered, and dried to obtain the high-impact ASA rubber powder.

2. The preparation method according to claim 1, characterized in that: In step (1)-step (2), the reducing agent is selected from at least one of sodium thiosulfate, EDTA, and ammonium ferrous sulfate, preferably EDTA.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of butyl acrylate to ethyl methacrylate is 50-500:0.1-5, preferably 60:

1.

4. The preparation method according to claim 1, characterized in that: In step (2), the added mass of the butyl acrylate, ethyl methacrylate, emulsifier, cross-linking agent, initiator and reducing agent is 1 / 4 to 2 times, preferably 3 / 4 times, the added mass of the butyl acrylate, ethyl methacrylate, emulsifier, cross-linking agent, initiator and reducing agent in step (1), respectively.

5. The preparation method according to claim 1, characterized in that: In step (3), the total mass ratio of the styrene, acrylonitrile and butadiene to the total mass ratio of the butyl acrylate and ethyl methacrylate in step (1) is 1:2-15, preferably 1:

4.

6. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of styrene, acrylonitrile and butadiene is 3-10:2-8:0.01-0.5, preferably 8:7:0.

25.

7. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of the total mass of methylsiloxane and polyethylene terephthalate to the mass ratio of the butyl acrylate in step (1) is 1:100-1000, preferably 1:

400.

8. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of methylsiloxane to polyethylene terephthalate is 1-10:1, preferably 3:

1.

9. A composite material, characterized in that: The composite material comprises high-impact ASA rubber powder prepared according to the preparation method of any one of claims 1 to 8, SAN resin, antioxidant and dispersant; preferably, the composite material comprises, in parts by weight: 10-20 parts of high-impact ASA rubber powder prepared according to the preparation method of any one of claims 1 to 8, 8-15 parts of SAN resin, 0.5-1.5 parts of antioxidant and 0.1-0.5 parts of dispersant.

10. The method for preparing the composite material according to claim 9, characterized in that: The method comprises the following steps: uniformly mixing the formulated amount of high-impact ASA rubber powder, SAN resin, antioxidant and dispersant, and extruding and granulating by using a twin-screw extruder.

Citation Information

Patent Citations

  • ASA (acrylonitrile-styrene-acrylate) resin with favorable appearance performance and preparation method thereof

    CN102161808A

  • ASA rubber powder, preparation method thereof and highlight ASA resin

    CN117510737A